Remarks on the occurrence of ornamentation of a byzantine character on weapons and wooden implements, made by the natives of an African Tribe, on the Coast of the Red Sea (Proceedings of the Society of Antiquaries of Scotland, 1852)
Alexander Christie, Esq., exhibited several specimens of workmanship from Aden. The most informative of which were a set of large, ornamented wooden spoons. These had been decorated in a style similar to that seen on sculptured standing stones in Scotland and ecclesiastical relics in Scotand and Ireland, prior to the 12th century. By this and evidence culled from an account of the tribe that executed the carvings, Mr. Christie proposed that these people were descended from a branch of the ancient African Church.